2001
DOI: 10.1182/blood.v97.10.3061
|View full text |Cite
|
Sign up to set email alerts
|

The relative quiescence of hematopoietic stem cells in nonhuman primates

Abstract: Quiescence has been thought to be required for the retention of the full biological potential of pluripotent hematopoietic stem cells (PHSCs). This hypothesis has been challenged recently by the observation that all murine PHSCs cycle continuously and constantly contribute to steadystate blood cell production. It was asked whether these observations could be extrapolated to describe hematopoiesis in higher mammals. In this series of experiments, the replicative history of PHSCs was examined in baboons by conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 54 publications
2
54
0
Order By: Relevance
“…The rate of hematopoietic stem cell (HSC) cycling in small rodents was estimated at 30 days by 5-bromodeoxyuridine (BrdU) labeling 8 and up to 1 year in nonhuman primates. 9 Similar cycling kinetics have also been observed in other stem cell types such as mouse cornea epithelia 10 and hair follicles. 11 In the skin, four times as many dermal stem cells are in the S-G 2 /M phases of the cell cycle as compared to more primitive dermal cells.…”
Section: Adult Stem Cells and The Cell Cyclesupporting
confidence: 62%
“…The rate of hematopoietic stem cell (HSC) cycling in small rodents was estimated at 30 days by 5-bromodeoxyuridine (BrdU) labeling 8 and up to 1 year in nonhuman primates. 9 Similar cycling kinetics have also been observed in other stem cell types such as mouse cornea epithelia 10 and hair follicles. 11 In the skin, four times as many dermal stem cells are in the S-G 2 /M phases of the cell cycle as compared to more primitive dermal cells.…”
Section: Adult Stem Cells and The Cell Cyclesupporting
confidence: 62%
“…The BM was diluted 1:8 in Dulbecco's phosphate-buffered saline (DPBS; Invitrogen Corporation, San Diego, CA) and the mononuclear cell (MNC) fraction was isolated by centrifugation over a 60% Percoll (Pharmacia, Uppsala, Sweden) density gradient at 500g for 30 minutes at room temperature (RT) [19]. The MNC fraction was collected and cultured in MSC growth media (MSCGM, Lonza, Inc., Walkersville, MD) at a density of 4,000 cells/cm 2 and allowed to proliferate.…”
Section: Baboon Msc Isolation and Characterizationmentioning
confidence: 99%
“…On the other hand, long-term in vivo BrDU labeling experiments indicate that in mice (Bradford et al, 1997;Pietrzyk et al, 1985) and to a lesser degree in primates (Mahmud et al, 2001) hematopoietic stem cells are constantly and slowly cycling. In mice continual BrDU administration demonstrated that Ho-lo/Rho-lo primitive HSC cycle with an average turnover time of 30 days.…”
Section: The Cell Cycle Status Of Hematopoietic Stem Cellsmentioning
confidence: 99%